Available sulphur by different extractants in soils of the state of Ceará, Brazil - Catia Pereira Uchôa, Sandra; Felipe Ferreyra Hernández, Fernando; Ferreira Melo, Valdinar; Cristina Oliveira da Silva, Deyse; José da Silva, Armando; de Brito Carvalho, Laís (Revista Ciência Agronômica, 2021)
Despite the relevance of sulphur (S) to plant development, studies in Brazil on its availability in the soil arerestricted to a few crops and regions. The aim of this study was to compare extractants for assessing the availability of S, andestablish critical levels for soils in the state of Ceará. In the laboratory, available S was extracted from 23 soils (0 - 0.20 m),using two extractants: a solution of Ca(H2PO4)2, 500 mg L-1 P in H2O (MCP) and NH4OAc in HOAc (AMA). In an experimentset up in a greenhouse, forage sorghum ‘EA116’ (Sorghum vulgari Pers.) was used as an indicator plant in two successive crops.A completely randomised experimental design was employed, in a 23 x 2 factorial scheme with three replications, where thefactors corresponded to the soils and to the doses of S (0 and 80 mg per experimental unit). The MCP was more efficient inextracting available S than was the AMA, although the S content obtained by both did show a significant correlation (r = 0.96).The available S using MCP showed a better correlation, with an increase in production and in absorbed S, suggesting MCP tobe the most suitable extractant. The critical levels for S were 3.90 and 3.40 mg dm-3 for MCP and AMA, respectively.